Football and stereotypes: narratives of difference between Argentina and Brazil - Alabarces, Pablo Alejandro (2018)
Through an analysis of football, this work explores how stereotypes such as tropicalism and Europeanism are used to construct narratives of national identity in Argentina and Brazil. These stereotypes, which are the consequence of colonial perspectives that seek to reduce heterogeneity in order to gain symbolic power, appear to be effective when we consider their prominence in a range of media. This study argues that these stereotypes need to be deconstructed using methodologies based in the social sciences, while also considering the role of humour in their production and dissemination.